Challenges to the multilateral trading system and possible responses - Arvind Panagariya (Kiel Institute for the World Economy (IfW), 2013)
This paper develops three major themes. First, the atmosphere of gloom around the multilateral trading system due to dim prospects of a successful conclusion of the Doha Round notwithstanding, global trade regime remains open and the institution in charge of it, the World Trade Organization, is in sound health. If anything, the Doha Round has been a victim of its own success: considerable de facto liberalization in agriculture has been achieved since the launch of the round. Second, to secure the future of the multilateral trading system, it is nevertheless crucial that the Doha Round is brought to a conclusion even if in a highly diluted form. The damage to the system from an outright failure will be very substantial. Finally, closing the Doha Round will require the United States leading the negotiations. Suggestions that as the largest merchandise exporter, China should now take the lead are frivolous.
Keywords: F13; F15; 330; World Trade Organization; Doha Round; multilateralism; regionalism